IMPLEMENTASI E-GOVERNMENT DALAM PELAYANAN PUBLIK (STUDI DI KANTOR DESA KEDUNGASRI KECAMATAN TEGALDLIMO KABUPATEN BANYUWANGI) - M. Alfin Ardhani; Dimas Imaniar; Andhika Wahyudiono (Yayasan Nusantara Hasana Berdikari, 2024)
One information technology that has a big influence on human life, especially in Indonesia, is the application of electronic government (e-government). E-government aims to achieve transparency in public services by integrating electronic systems for managing and processing documents and information. Bureaucratic reform often stems from poor public service quality, leading governments to introduce e-government solutions for enhancing public services to meet public expectations. So, the researcher will highlight the core issue of the study, which is the suboptimal execution of e-government in public services to align with public expectations. This study employs a descriptive research method utilizing a qualitative approach. The selection of this approach is driven by the objective of comprehending and detailing the deployment of e-government in public services within Kedungasri Village, Tegaldlimo District, Banyuwangi Regency, along with the challenges it faces. The implementation of e-government in Kedungasri Village, Tegaldlimo, Banyuwangi is quite good and smooth. This can be seen from a beneficial perspective for society. Key elements for successful e-government implementation include a smooth system and smooth network, making it easier to access the existing e-government system. The inhibiting factor in implementing e-government is many Kedungasri sociey are technologically illiterate and do not have cellphones. By introducing e-government in Kedungasri Village, there is an expectation for increased awareness and education on utilizing information and communication technology so that its implementation can run even better. It is hoped that all village officials will maximize their efforts to support the community and participate in training with more focus so that they can better serve the community.